Blind Adaptive Linear Parallel Interference Canceller for DS-CDMA in Frequency Selective Fading Channels - Vinhoza, T.T.V.; de Lamare, R.C.; Sampaio-Neto, R. (2006 IEEE Ninth International Symposium on Spread Spectrum Techniques and Applications, 2006)
In this work we propose an adaptive blind linear parallel interference canceller (PIC) for direct-sequence code division multiple access (DS-CDMA) systems in frequency selective fading channels. A code-constrained constant modulus (CCM) design criterion based on constrained optimization techniques is proposed for PIC detectors in scenarios subject to multipath, and computationally efficient blind adaptive stochastic gradient (SG) and recursive least squares (RLS) algorithms are described for estimating both the receiver and channel parameters. Simulation results for an uplink scenario assess the algorithms, the proposed blind adaptive PIC detectors against existing receivers and evaluate the effects of error propagation of the new cancellation techniques